Distribution Strategy Analysis to Increase Sales Excellence at PT Bintang Sidoraya - Arief Bustaman, Jauhari; Hidayat, Anas (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2023)
This study aims to conduct an analysis related to distribution strategies to increase sales excellence at PT Bintang Sidoraya. This study uses a qualitative approach in the form of interviews, observations, and documentation as the primary data collection. The analysis used in research is in the form of case studies that aim to explore real life, contemporary limited systems, or various limited systems. The results of the analysis show that the application of STP by utilizing various advantages and can also reduce existing weaknesses produces competitive advantages, as well as the application of 4P (product, price, promotion, and place) through providing good product quality, providing affordable prices, promoting through pamphlets, banners, and WOM (word-of-mouth marketing, and placing supermarkets as points of sale to customers connected by salesperson, administration manager, and warehouse manager.